Discussion of Determinants of Auditor Expertise - Marchant, Garry (Journal of Accounting Research, 1990)
Bonner and Lewis investigate the determinants of auditor expertise by examining the roles of various types of knowledge and ability in auditor performance. They conclude that differences in knowledge and ability better explain variance in task performance than does experience. The paper is an innovative step in developing an understanding of auditor expertise. Bonner and Lewis are the first auditing researchers to elaborate what elements might determine expert performance in a number of different auditing tasks and to provide an estimate of the relative importance of those elements in each task. Their paper prompted a broad discussion of auditor expertise and its measurement by conference participants. This paper summarizes and extends that discussion by focusing on the two main issues raised: (1) What is expertise in auditing? and (2) How can an auditing expert be identified?